Exploring the educational needs of nurses on children's pain management: A descriptive qualitative study. Issue 3 (18th February 2020) - Kusi Amponsah, Abigail; Kyei‐Dompim, Joana; Bam, Victoria; Kyei, Evans F.; Oduro, Evans; Ahoto, Collins K.; Axelin, Anna
Abstract: Aim: To explore the educational needs of nurses on children's pain management. Design: A descriptive qualitative study. Methods: Individual and group interviews were conducted among 28 nurses and four nurse managers at four hospitals in the Ashanti region of Ghana. The recorded interviews were later transcribed verbatim and thematically analysed based on a conceptual interest in the educational needs on paediatric pain management. Results: Nurses were acquainted with pain assessment of children who can verbally communicate. They mainly used drugs in treating pain and were familiar with the use of some non‐pharmacological interventions. Notwithstanding, they desired to know more about pain assessment for children with non‐functional speech. Additionally, they were interested in learning more about both drug and nondrug pain relief methods for children. The sampled nurses and nurse managers indicated diverse preferences on the nature of the paediatric pain educational programme based on their personal choices and working dynamics.